Sinergi Gerakan, Budaya, dan Literasi: Brain Gym berbasis Budaya sebagai Pendekatan Multisensoris untuk Siswa Slow Learner - Annisa, Nuri; Sunendar, Dadang; Agustin, Mubiar (Jurnal Sporta Saintika, 2024)
Students from diverse cultural and social backgrounds require distinct learning approaches, particularly for slow learners. Learning approaches are designed to be more creative and inclusive in order to anticipate problems in the learning process. This study investigates the use of a Culture-based Brain gym as one of the attempts and solutions for boosting slow learners' reading skills. This study employs a qualitative method and a case study methodology to chronicle and describe how students who are slow learners engage in reading activities during the daily learning process. Data were collected by observation and in-depth interviews with 18 informants from twelve different schools. The study's findings revealed that slow learners were interested in learning to read by combining elements of Brain gym and culture. This culture-based Brain gym exercise improved students' reading skills by strengthening attitudes and awareness of the importance and interest in reading activities.